The validation of the Italian version of multiple sclerosis neuropsychological screening questionnaire in Huntington’s disease - Migliore, Simone; D’Aurizio, Giulia; Ceccarelli, Consuelo; Casella, Melissa; Curcio, Giuseppe; Squitieri, Ferdinando (Neurological sciences, 2023)
Introduction Multiple sclerosis neuropsychological questionnaire (MSNQ) is a brief questionnaire useful for screening patient’s and informant’s self-perception of cognitive dysfunctions in daily life activities. Our study aims to evaluate the MSNQ validity in Huntington’s disease (HD) mutation carriers and to correlate MSNQ scores with neurological, cognitive, and behavioral variables. Methods The study was conducted on a sample of 107 subjects from presymptomatic to the middle stage of HD recruited at LIRH Foundation and C.S.S. Mendel Institute in Rome. Unified Huntington’s Disease Rating Scale (UHDRS), an internationally standardized and validated scale, was used to evaluate motor, functional cognitive, and behavioral domains. Results Our results showed that in HD subjects, MSNQ has a unidimensional factor structure. Correlational analyses indicated a good correlation between the MSNQ-patient version (MSNQ-p) and clinical variables, specifically with cognitive dysfunction and behavioral alterations. Moreover, higher scores in MSNQ-p were associated with higher motor disease and functional impairment showing that patients in advanced stage of HD perceive a greater cognitive impairment. These results confirm the questionnaire’s reliability. Conclusions The present study demonstrates the validity and adaptability of MSNQ in the HD population proposing it as a cognitive tool during routine clinical follow-ups, although further research is needed to determine an optimal cut-off score for this measure.